PERAN EKSTRAKURIKULER DALAM PENINGKATAN KOMPETENSI SISWA DI SEKOLAH DASAR - Oktavia Wahyuni, Siva; Sadasa Putra, Karantiano; Nurjamaludin, Muhammad; Aviatunnur, Siddikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Effective management of students in extracurricular programs is key to successfully enhancing students’ personal competencies to the fullest extent. Extracurricular programs become a forum to support the development of students' skills, both academic and non-academic, including social, emotional, and character skills. This research aims to analyze more deeply about extracurricular programs in order to develop student competencies. This study employed a qualitative method, and the data were obtained from interviews with the principal, homeroom teachers, and subject teachers at SDN 3 Sukagalih. The results showed that: 1). The implementation of extracurricular programs has a positive impact on improving student competence, both from academic and non-academic aspects, and 2). Factors supporting the success of the program include school commitment, active involvement of students, and support from parents. However, there are some obstacles such as time constraints and lack of resources or facilities. Thus, it can be concluded that extracurricular activities make a significant contribution to the overall development of elementary school students’ competencies. Therefore, schools are expected to manage and develop extracurricular programs effectively to support the achievement of educational goals.